The bacterial quorum sensing molecule, 2-heptyl-3-hydroxy-4-quinolone (PQS), inhibits signal transduction mechanisms in brain tissue and is behaviorally active in mice. (August 2021) - Di Menna, L.; Busceti, C.L.; Ginerete, R.P.; D'Errico, G.; Orlando, R.; Alborghetti, M.; Bruno, V.; Battaglia, G.; Fornai, F.; Leoni, L.; Rampioni, G.; Visca, P.; et al.
Abstract: Interkingdom communication between bacteria and host organisms is one of the most interesting research topics in biology. Quorum sensing molecules produced by Gram-negative bacteria, such as acylated homoserine lactones and quinolones, have been shown to interact with host cell receptors, stimulating innate immunity and bacterial clearance. To our knowledge, there is no evidence that these molecules influence CNS function. Here, we have found that low micromolar concentrations of the Pseudomonas aeruginosa quorum sensing autoinducer, 2-heptyl-3-hydroxy-4-quinolone (PQS), inhibited polyphosphoinositide hydrolysis in mouse brain slices, whereas four selected acylated homoserine lactones were inactive. PQS also inhibited forskolin-stimulated cAMP formation in brain slices. We therefore focused on PQS in our study. Biochemical effects of PQS were not mediated by the bitter taste receptors, T2R4 and T2R16. Interestingly, submicromolar concentrations of PQS could be detected in the serum and brain tissue of adult mice under normal conditions. Levels increased in five selected brain regions after single i.p. injection of PQS (10 mg/kg), peaked after 15 min, and returned back to normal between 1 and 4 h. Systemically administered PQS reduced spontaneous locomotor activity, increased the immobility time in the forced swim test, and largely attenuated motor response to the psychostimulant, methamphetamine. These findings offer the first demonstration that a quorum sensing molecule specifically produced by Pseudomonas aeruginosa is centrally active and influences cell signaling and behavior. Quorum sensing autoinducers might represent new interkingdom signaling molecules between ecological communities of commensal, symbiotic, and pathogenic microorganisms and the host CNS. Graphical Abstract: ga1